FOXO1 regulates pentose phosphate pathway-mediated induction of developmental erythropoiesis - Monsalve, Anuntxi; Canals, Isaac; Oburoglu, Leal (Frontiers in Cell and Developmental Biology, 2022)
Primitive, neonatal and adult erythroid cells have been previously shown to have an active pentose phosphate pathway (PPP) that fuels various processes. However, it is unclear whether the PPP plays a role during the emergence of erythroid progenitors from hemogenic endothelium (HE). In this study, we explored PPP and its genetic regulation in developmental erythropoiesis. We induced hematopoietic differentiation of human induced pluripotent stem cells (hiPSCs) to obtain HE cells. These cells were treated with lentiviral vectors harboring shRNAs against FOXO1, or with inhibitors against the PPP, NRF2 or AKT. Erythroid differentiation, proliferation and frequency were evaluated by flow cytometry. Gene expression was assessed by qPCR or by analysis of available RNAseq data. We found that PPP is indispensable for the erythroid differentiation of HE cells and it partially fuels nucleotide biosynthesis. Moreover, we showed that NRF2 and AKT are essential, while FOXO1 is detrimental, for HE-derived erythroid differentiation. In contrast, blocking FOXO1 expression did not affect erythroid differentiation of cord-blood HSPCs. Mechanistically, FOXO1 inhibition in HE cells led to an increase in the non-oxidative branch of the PPP. Erythroid differentiation resulting from human HE cells depends on the downregulation of FOXO1 and expression of AKT and NRF2. During developmental erythropoiesis, the gradual decrease in FOXO1 activates the PPP and fuels nucleotide biosynthesis and cell proliferation.